Development of thalamocortical projections in the South American gray short-tailed opossum (Monodelphis domestica). - Molnár, Z; Knott, G; Blakemore, C; Saunders, N (1998)
We determined the time-course and general pattern of thalamocortical development of Monodelphis domestica by tracing projections with carbocyanine dye in fixed postnatal brains between postnatal day 2 (P2) and P30. By P2, the first neurons have migrated to form the preplate of the lateral cortex and have sent out axons into the intermediate zone. By P3, fibers from the preplate of more dorsal cortex have entered the intermediate zone, and, by P5, they reach the primitive internal capsule. Crystal placements in the dorsal thalamus at P2-P3 reveal thalamic axons extending down through the diencephalon and growing out through the internal capsule among groups of back-labelled cells that already project into the thalamus. Thalamic axons arrive at the cortex after the arrival of cells of the true cortical plate has split the preplate into marginal zone and subplate. Axons from the ventral part of the dorsal thalamus reach the lateral cortex by P5: Dorsal thalamic fibers arrive at the extreme dorsal cortex by P9. The deeper layers of the cortex appear to mature relatively earlier in Monodelphis than in eutherian mammals, and the subplate becomes less distinct. Thalamic fibers and their side branches proceed into the cortex without an obvious period of waiting in the subplate, but they do not penetrate the dense cortical plate itself. Monodelphis could provide an excellent model species, because the development of its thalamocortical connections is entirely an extrauterine process: The period P0-P15 corresponds to that of E12-P0 in the rat.